2001
DOI: 10.3168/jds.s0022-0302(01)74696-6
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Pasture to Lactating Holsteins Fed a Total Mixed Ration Diet

Abstract: Beginning in September 1997, a 6-week study was conducted to compare performance and income-over-feed cost of lactating Holsteins cows fed either a total mixed ration diet (TMR) only, compared to TMR in the afternoon and pasture in the morning, or TMR in the morning and pasture in the afternoon. Fifty-four Holstein cows in midlactation, averaging 28.1 kg/d of milk, were used in the study. Cows were on pasture for 8 h/d after either the p.m. or the a.m. milking. Predominantly orchardgrass with lesser amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 14 publications
4
47
1
1
Order By: Relevance
“…The same trend with higher MU during the summer months (July to September) has been reported by several authors (Godden et al, 2001;Rajala-Schultz and Saville, 2003;Wattiaux et al, 2005). This fluctuation could reflect the grazing period and the access of cows to fresh pasture, which typically contains highly degradable protein and has a high protein-to-energy ratio (Soriano et al, 2001). Moreover, this seasonal effect varied from year to year; the MU level increased slightly across years.…”
Section: Datasupporting
confidence: 54%
“…The same trend with higher MU during the summer months (July to September) has been reported by several authors (Godden et al, 2001;Rajala-Schultz and Saville, 2003;Wattiaux et al, 2005). This fluctuation could reflect the grazing period and the access of cows to fresh pasture, which typically contains highly degradable protein and has a high protein-to-energy ratio (Soriano et al, 2001). Moreover, this seasonal effect varied from year to year; the MU level increased slightly across years.…”
Section: Datasupporting
confidence: 54%
“…Soriano et al (2001) in Holstein cows and Soryal et al (2004) in Alpine goat also found that pasture feeding slightly increased the milk fat, protein and solid without fat contents and decreased the lactose content. These results suggested that the milk produced by the grazed group would have a higher cheese yield.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies that compared cows housed indoors and continuously on pasture reported lower BW, milk production and milk protein in the case of grazing cows (HernandezMendo et al, 2007;Kolver and Muller, 1998). Soriano et al (2001) reported that cows kept on pasture 8 h/day after either the morning or afternoon milking consumed less TMR compared to when they were indoors, and produced less milk than cows kept indoors. In contrast, the cows in our study were able to consume TMR during the daylight hours, when they are highly motivated to eat (DeVries et al, 2003), and thus were able to maintain similar intakes to those cows housed indoors continuously.…”
Section: Discussionmentioning
confidence: 92%
“…Even with ideal pasture conditions, the lower nutrient density of grass relative to more concentrated feeds provided indoors will likely reduce milk production for pasture-housed animals (Soriano et al, 2001). Previous work in our group has shown indoor group housed dairy cows consume more than 80% of their daily DMI from 0700 to 2000 h (Huzzey et al, 2007) and that when provided free access to pasture, they normally choose to stay indoors during the day and move outdoors to pasture at night (Legrand et al, 2009).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%